Amazigh Language Use on Social Media: An Exploratory Study - Brahim Ait Laaguid; Azeddine Khaloufi (JURNAL ARBITRER, 2023)
This paper aimed to investigate Moroccan Amazighs’ use of the Amazigh language on social media and the various aspects of Amazigh’s presence on these platforms. The study was carried out following a descriptive research design whereby data were collected by way of a large-scale online survey. A sample of one-thousand informants was randomly selected from all over Morocco based on several social variables, including sex, age, education, and region of belonging. Data analysis revealed that the Tifinagh script is less used compared to Latin and Arabic in which the language is highly present on social media platforms. It was also found that Amazigh is greatly used in chatting and that Moroccans highly interact with Amazigh-related content on Amazigh public pages and groups on social networking websites. The survey respondents accordingly showed remarkable satisfaction with social media content published in Amazigh. The analysis also demonstrated that Amazigh social media users are particularly interested in topics pertinent to the fields of history, culture, and art. It was yet discovered that Moroccans view the use of Amazigh on social networking sites as an effective alternative for promoting and improving the language. The study calls for upholding and ameliorating online Amazigh language use, as well as extending its scope by adopting digitization policies centering on the prominence of Tifinagh.